Analysis of the nutritional status in the Palestinian territory: a review study - A. Assaf, Enas; Al Sabbah, Haleama; Al-Jawadleh, Ayoub (Frontiers in Nutrition, 2023)
Background: Food insecurity, occupation, and poverty contribute to the poor nutritional status in Palestine. This review study aimed to analyze the nutrition situation in the Palestinian Territory using the published data from 2011 to 2023.Searching for relevant publications yielded 67 studies. Based on reviewing these studies, five major themes were identified, namely; low birth weight, breastfeeding, obesity and overweight, protein-energy malnutrition, and micronutrient deficiency.Results: Based on reviewing these studies, five major themes were identified, namely; low birth weight, breastfeeding, obesity and overweight, protein-energy malnutrition, and micronutrient deficiency. Based on the literature, the prevalence rate of exclusive breastfeeding was 24.4% in the Gaza Strip compared to a national rate of 39.9% in 2020. Smoking, anemic mothers, diet during pregnancy, and indoor pollution were associated with low birth weight. One-fifth of the boys and girls showed stunting by two years of age in the Gaza Strip, and girls were more stunted than boys. The prevalence rates of underweight, overweight, and obesity among school children in the West Bank were 7.3%, 14.5%, and 15.7%, respectively. Age, gender, and living area were significant predictors of being overweight among school children. The prevalence rates of overweight and obesity among adults in Palestine were 57.8% and 26.8%, respectively. Obesity is associated with a family history, chronic diseases, and low physical activity among adults. Exclusive breastfeeding was below the WHO recommendations, and high prevalences of obesity and overweight were found among children and adults. Iron-deficiency anemia (IDA) among pregnant women and children remains a challenging public health issue, while other micronutrients deficiency were high among children.Palestinian Territory 2 This is a provisional file, not the final typeset article Conclusion: This review emphasizes the necessity for multi-sectoral interventions to address malnutrition and nutrition shifts. It highlights the gaps and addresses the nutritional-related problems in the Palestinian Territory, which can serve as a basis for guiding the United Nations agencies and governments in developing evidence-based policies and strategies in prioritizing nutritional interventions to meet sustainable development Goals.